Improved modulated model‐predictive control for PMSM drives with reduced computational burden. Issue 14 (1st November 2020) - Sun, Tianfu; Jia, Chengli; Liang, Jianing; Li, Ke; Peng, Lei; Wang, Zheng; Huang, Hui
Abstract : In this paper, an improved modulated model‐predictive control (MMPC) scheme is proposed for the current control of permanent magnet synchronous motors (PMSMs). Different from the existing MMPC based motor current control schemes which simply feed the resultant voltage vectors calculated by the finite‐control‐set model predictive control (FCS‐MPC) to the SVPWM module and could not adjust the current control bandwidth, the principle of the proposed MMPC current control scheme is to control the current vector along a predefined trajectory and the resultant current vector is expected to equal the reference current vector at the end of the predictive horizon. Therefore, the control bandwidth of the proposed MMPC can be easily adjusted via the predictive horizon, and the transient performance of the current control can be improved without current overshoot. Moreover, different from existing MMPCs, the proposed control scheme does not need to predict all the resultant currents generated by the basic voltage vector combinations of the six voltage sectors, but only needs to predict the resultant currents generated by the basic voltage vector combinations of three voltage sectors. Therefore, the computational burned is significantly reduced.